Fast XYT imaging of elementary calcium release events in muscle with multifocal multiphoton microscopy and wavelet denoising and detection. - von Wegner, Frederic; Both, Martin; Fink, Rainer; Friedrich, Oliver (IEEE Transactions on Medical Imaging, 2007)
We used multifocal multiphoton microscopy to image fast, localized elevations of the cytosolic Ca2+ concentration in two spatial dimensions plus time (XYT). This technique extends the common spatially 1-D XT imaging and allows the acquisition of more than ten times longer time series (>500 images) and ten times larger areas of interest than for previously used confocal XYT imaging techniques due to lower phototoxicity and fast multifocal scanning. We recorded spontaneously occurring elementary Ca2+ release events in chemically permeabilized adult mammalian skeletal muscle fibers using two-photon excitation of the fluorescent dye Fluo-4. The resulting time series were analyzed with an automated denoising and detection algorithm based on the à trous implementation of the discrete wavelet transform. Wavelet coefficient hard-thresholding is used for denoising and event detection is performed across several wavelet scales. The spatiotemporal characteristics of the detected Ca2+ release events are followed throughout the XYT stack and are parametrized using a biophysically valid anisotropic Gaussian event model. The proposed method allows a detailed spatiotemporal analysis of elementary Ca2+ release events underlying the excitation-contraction coupling process in muscle.
Keywords: biomedical optical imaging; calcium; cellular biophysics; image denoising; muscle; optical microscopy; wavelet transforms